Improvement of methodology for determining the types of higher nervous activity in pigs - Замазій, А. А.; Камбур, М. Д.; Піхтірьова, А. В. (Scientific Progress & Innovations, 2013)
The data on the improvement of the methodology for determining the types of higher nervous activity in pigs are given in the article. The essence of the alimentary-motor technique is to create a series of motor responses that determine the properties of the nervous system of each animal separately. To determine the type of higher nervous activity of sow, you must determine balance and mobility of nervous processes. The definition of typological characteristics of the nervous system of sows can be realized by this method in a production environment familiar for animals (in the pigsty), with no arrangement of arena (ground) and the use of special equipment. It is not stressful and traumatic for sows.